2019
DOI: 10.3390/su11184834
|View full text |Cite
|
Sign up to set email alerts
|

A Tax Coming from the IPCC Carbon Prices Cannot Change Consumption: Evidence from an Experiment

Abstract: This article compares a socially-optimal tax coming from a model integrating consumers’ preferences for various milks, with a tax directly computed from carbon emissions of milks with carbon prices given by the International Panel for Climate Change (IPCC). Regarding consumers’ preferences, we conducted an experiment in France for finding consumers’ willingness-to-pay (WTP) for different bottles coming from either cow’s milk or soy milk, under a regular or an organic process of production. This experiment show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Consumers are willing to accept technological innovations in traditional products if the innovation is perceived risk-free and if the product is not too distorted, in its image, in its quality with "pure" ingredients and/or in its taste (Braghieri et al, 2014;Lengard et al, 2011;Pilone et al, 2015). The integrity of food components is crucial for guaranteeing a relatively high WTP, a result previously verified with milk coming from cow or from plant-based substitutes such as soy or almond "milks" (Yokessa and Marette, 2019). This differs from studies focusing on WTP for genetically modified organisms or gene editing, in which messages on these technologies systematically lead to a sharp decline in WTP for specific foods (Lusk et al, 2005;Colson and Rousu, 2013;Lin et al, 2019;Caputo et al 2020;Marette et al, 2021).…”
Section: Reaction Toward the New Processmentioning
confidence: 99%
“…Consumers are willing to accept technological innovations in traditional products if the innovation is perceived risk-free and if the product is not too distorted, in its image, in its quality with "pure" ingredients and/or in its taste (Braghieri et al, 2014;Lengard et al, 2011;Pilone et al, 2015). The integrity of food components is crucial for guaranteeing a relatively high WTP, a result previously verified with milk coming from cow or from plant-based substitutes such as soy or almond "milks" (Yokessa and Marette, 2019). This differs from studies focusing on WTP for genetically modified organisms or gene editing, in which messages on these technologies systematically lead to a sharp decline in WTP for specific foods (Lusk et al, 2005;Colson and Rousu, 2013;Lin et al, 2019;Caputo et al 2020;Marette et al, 2021).…”
Section: Reaction Toward the New Processmentioning
confidence: 99%
“…Data on environmentally impacting emissions and resource use from PB drinks versus milk was found in 13 studies. The system boundaries in these studies varied from cradle to processing [16,17,37,48], cradle to retailer/wholesaler [36,40], and cradle to consumer [4,39,[41][42][43]49]. In two studies, there was no explanation of the system boundaries [42,51].…”
Section: Pb Beverages Compared To Milkmentioning
confidence: 99%
“…The system boundaries in these studies varied from cradle to processing [16,17,37,48], cradle to retailer/wholesaler [36,40], and cradle to consumer [4,39,[41][42][43]49]. In two studies, there was no explanation of the system boundaries [42,51]. Scheelbeck et al [51] who calculated both nutrition, GHG emissions, the blue water footprint (ground and surface water) for a range of foods and diets referred to a large number of individual studies of greenhouse gas emissions from various foods as well as data from the Water Footprint Network (WFN) for water use.…”
Section: Pb Beverages Compared To Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Tax pricing in its different forms and shapes offers in theory the easiest way to reduce GHG emissions, but policymakers and institutions are not yet able to develop efficient and cost-effective instruments to put a price on the social costs of emissions. Furthermore, studies and experiments on PCC Carbon Prices, as well as on Product Attributes (9) and WTP showed that tax based on the IPCC carbon prices cannot change consumption and seem too weak for efficiently changing the consumption towards sustainable products (10).…”
Section: Tax Reliefsmentioning
confidence: 99%